Clinical evaluation of EqualsTwo® under eye gel in the management of periorbital issues in pregnant and lactating women: an open-label study - Dhruv Zaveri; Kinjal Barot; Trupti Patel; Parth Joshi; Simran Sethi; Sunil S. Iyer; M. E. Kannan (International Journal of Research in Dermatology, 2026)
Background: Periorbital hyperpigmentation, puffiness, and fine lines are common dermatological concerns adversely impacting quality of life. Conventional therapies, including hydroquinone and retinoids have safety limitations in pregnant and lactating women, necessitating exploration of botanical alternatives. This study evaluated the safety and efficacy of a natural-origin EqualsTwo® under eye gel in improving periorbital concerns within this sensitive population. Methods: In this prospective, open-label, single-arm exploratory study, 72 women (12 pregnant, 60 lactating; aged 22-40 years) were enrolled; 65 completed the trial. Participants applied approximately 0.2 gm of the investigational product twice daily for 42 days. Dermatological assessments were performed using a 6-point grading scale for dark circles, Investigator's Global Assessment Scale for puffiness, and Allergan fine lines scale. Melanin concentration and fine-line metrics (count, length, width, depth) were assessed using the Antera 3D system, supported by subject-reported outcomes. Safety was monitored throughout. Results: By day 42, 55.38% of participants achieved grade 0 for both dark circles and puffiness, while 66.15% demonstrated minimal fine lines. Instrumental assessments revealed a 10.47% reduction in melanin concentration (p<0.0001), 32.36% decrease in fine-line count (p<0.0001), 86.22% reduction in line depth (p<0.0001), and 69.98% decrease in line width (p<0.0001). All participants reported visible improvements in hydration, softness, and firmness. 100% participants expressed satisfaction, and no adverse events were recorded. Conclusions: The investigation product demonstrated improvements across all periorbital parameters with no treatment related adverse events, supporting botanical formulations as effective alternatives in pregnant and lactating women.